2003
DOI: 10.1210/en.2003-0092
|View full text |Cite
|
Sign up to set email alerts
|

The FK506-Binding Immunophilin FKBP51 Is Transcriptionally Regulated by Progestin and Attenuates Progestin Responsiveness

Abstract: FKBP51 and FKBP52 are large molecular weight FK506-binding immunophilins that have diverse biochemical functions. Best studied is the role that they play as components of steroid hormone receptors. Differential display and gene array screens have identified FKBP51 as a progestin-inducible gene. Here we demonstrate progestin enhancement of FKBP51 mRNA and protein in T-47D cells. FKBP51 mRNA and protein levels were increased 3-fold by 20 nM R5020. Induction of FKBP51 mRNA was unaffected by 1 micro g/ml cyclohexi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
1

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 128 publications
(107 citation statements)
references
References 51 publications
2
104
1
Order By: Relevance
“…In the course of analyzing TPR expression levels in the tissues of wild type and Fkbp52-deficient mice, we found a dramatic down-regulation of Fkbp51 in Fkbp52-deficient penile tissue but not in the Fkbp52-deficient testis. Because Fkbp51 is a known target gene of AR action (29,32,33), this result was further evidence of compromised AR activity in the penis but not the testis. Moreover, since there is at least one report that Fkbp51 overexpression in prostate cells enhances AR activity (32), the interesting possibility was raised that a genetic interplay may exist between Fkbp52 and Fkbp51, perhaps for the purpose of regulating the tissue-selective functions of AR.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…In the course of analyzing TPR expression levels in the tissues of wild type and Fkbp52-deficient mice, we found a dramatic down-regulation of Fkbp51 in Fkbp52-deficient penile tissue but not in the Fkbp52-deficient testis. Because Fkbp51 is a known target gene of AR action (29,32,33), this result was further evidence of compromised AR activity in the penis but not the testis. Moreover, since there is at least one report that Fkbp51 overexpression in prostate cells enhances AR activity (32), the interesting possibility was raised that a genetic interplay may exist between Fkbp52 and Fkbp51, perhaps for the purpose of regulating the tissue-selective functions of AR.…”
Section: Discussionmentioning
confidence: 79%
“…Indeed, various groups have shown that Fkbp52 contributes to both the dynein interaction and hormone-induced translocation of GR (25)(26)(27). Meanwhile, a second line of inquiry has provided evidence for reciprocal control of GR and PR hormone binding function by Fkbp52 and Fkbp51, with Fkbp52 causing potentiation and Fkbp51 causing attenuation of this activity (15,28,29). These observations suggest a model in which differential incorporation of TPR proteins into SR com- and d) indicate the underdeveloped foreskin and ectopic urethral opening at the ventral aspect compared with normal morphology in controls (a and c).…”
Section: Androgen Receptor (Ar)mentioning
confidence: 99%
“…We extended this analysis to the regulation in T47D cells of progesterone target genes encoding IGFBP1, mucin 1 (MUC1) and FK506-binding protein 5 (FKBP51) (4,38,39) (Fig. 7).…”
Section: Function Of Lcor and Ctbp1 As Attenuators Of Progesteroneregmentioning
confidence: 99%
“…Remarkably, recruitment of FKBP51 as a cochaperone to Hsp90 protein complexes modulates the activity of other nuclear receptors, besides GR. 42,43 It is thus likely that SUMO conjugation to FKBP51 may impact on their activity as well. Further studies will be needed to address the overall significance of this mechanism on other nuclear receptors and in different contexts.…”
Section: Discussionmentioning
confidence: 99%